2017
DOI: 10.3847/1538-4357/aa8ee1
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Primordial Binary Evolution to the Two Blue-straggler Sequences in Globular Cluster M30

Abstract: Two blue-straggler sequences discovered in globular cluster M30 provide a strong constraint on the formation mechanisms of blue stragglers. We study the formation of the blue-straggler binaries through binary evolution, and find that binary evolution can contribute to the blue stragglers in both of the sequences. Whether a blue straggler is located in the blue sequence or red sequence depends on the contribution of the mass donor to the total luminosity of the binary, which is generally observed as a single st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 74 publications
3
33
0
Order By: Relevance
“…Indeed a few W Uma Variables (which are contact binaries) have been found along both the BSS sequences in M30 (Ferraro et al 2009) and NGC 362 (Dalessandro et al 2013). Using dedicated theoretical models, Jiang et al (2017) found that the contribution of the MT-BSSs to the blue or red sequence strongly depends on the contribution of the donor to the total luminosity of the unresolved binary system. Hence our observations further support the possibility that both collisional and MT-BSSs can populate the blue sequence.…”
Section: A Double Sequence Of Bssmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed a few W Uma Variables (which are contact binaries) have been found along both the BSS sequences in M30 (Ferraro et al 2009) and NGC 362 (Dalessandro et al 2013). Using dedicated theoretical models, Jiang et al (2017) found that the contribution of the MT-BSSs to the blue or red sequence strongly depends on the contribution of the donor to the total luminosity of the unresolved binary system. Hence our observations further support the possibility that both collisional and MT-BSSs can populate the blue sequence.…”
Section: A Double Sequence Of Bssmentioning
confidence: 99%
“…Recent Monte-Carlo simulations of synthetic MT-BSSs (Jiang et al 2017) showed that the blue-BSS sequence can be also populated by MT-BSSs. This finding by itself does not invalidate the possibility that the blue BSS sequence might be mainly populated by collisional BSSs, since the easiest way to reproduce the observed narrowness of the blue sequence and the adjacent gap is still the hypothesis that the vast majority of BSSs along this sequence formed almost simultaneously, instead as a result of a continuous process extending over a long time interval.…”
Section: Introductionmentioning
confidence: 99%
“…Ferraro et al (2009) discovered two BSS sequences in the optical CMD of GC M30, suggesting that the redder ones arise from the evolution of close binaries that are still experiencing MT which was in agreement with binary evolution models. Another explanation for the two BSS sequences in M30 was given by Jiang et al (2017) where they showed that binary evolution contributes to the formation of BSS in both sequences. Thus, identification of BSSs with hot companions using UV ob-servations are crucial to understanding their formation mechanism in binary systems.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the comparison with evolutionary models of BSSs formed by direct collisions of two MS stars (Sills et al (2009)) showed that the blue-BSS sequence is well fit by collisional isochrones with ages of ∼2 Gyr. Instead, the red-BSS population is far too red to be reproduced by collisional isochrones of any age, and it turned out to be compatible with the portion of the CMD where MT binary models are expected (Xin et al (2015), see also recent models by Jiang et al (2017) showing that MT-BSS might also "contaminate" the blue-BSS sequence). However the impressive agreement of the blue-BSS with the COLL isochrones suggests that the vast majority of these stars have a collisional origin and they are nearly co-eval possibly generated by short-lived event (the Core Collapse -CC).…”
Section: Exploring the Post Core Collapse (Pcc) Phasementioning
confidence: 97%